Variability in the Homeopathic Treatment of COVID-19 Patients: Findings of the Clificol International Clinical Case Registry - Yvonne Fok; Robbert van Haselen; Aaron To; Alexander Tournier (Integrative Medicine Reports)
Background: The Clificol® COVID-19 Support Project is an innovative international data collection project aimed at tackling some of the core questions in homeopathy, including the aspect of treatment individualization. This article further analyzes the symptoms used and remedies prescribed. Methods: We conducted an international clinical case registry study (ClifiCol) of patients with confirmed or suspected COVID-19. In China, the symptoms were collected with the aid of a questionnaire, whereas, in all the other countries, participating homeopaths could freely record the symptoms that informed the remedy prescription. The symptom rubrics and remedies used in non-Chinese countries were further analyzed. Results: The database consisting of 1227 cases, as collected between January 10, 2020, and October 31, 2021, was used as a basis for the analyses. It included 868 cases (1354 prescriptions) from 29 non-Chinese countries. We observed an unexpectedly high level of variability. This was expressed, among others, by the very large number of repertory rubrics used in general. In total, 1190 of the 1403 rubrics (85%) were used less than five times. A higher proportion of uncommon rubrics was not associated with faster recovery from COVID-19. In total, 137 homeopathic remedies were used; the three most frequently used ones (Bryonia alba, Phosphorus, and Arsenicum album) were used in 42% of all prescription episodes. The 88 least commonly used remedies (out of a total of 137) accounted for only 9% of all prescription episodes. Conclusions: A small subset of the most commonly used symptom rubrics and remedies covered the great majority of prescriptions. Focusing on the most common symptoms and remedies for the statistical validation of homeopathy is justified and will greatly enhance the ability of clinical case registry projects to contribute to improving homeopathic practice.